The effect of malotilate, a derivative of malotilate and a flavenoid on eicosanoid production in inflammatory bowel disease in rats - A. P. M. van Dijk; J. H. P. Wilson; F. J. Zijlstra (Hindawi Limited, 1993)
Acetic acid induced colitis in rats was used to investigate the effects of malotilate, a drug which has been shown to inhibit 5-1ipoxygenase in human macrophages, the malotilate derivate ZY16268 and the flavenoid ZY16369 on the eicosanoid production and the colonic morphology in inflammatory bowel disease. Acetic acid produced an acute inflammatory response in the colon, associated with a markedly raised inflammation score (15.8 vs. < 0.5), based on a seven-scaled scoring system which includes observation of haemorrhage, submucosal oedema, cellular infiltration, goblet cell depletion, loss of architecture, crypt abscesses and serosal involvement, of which every item was subdivided as mild, moderate and severe. Incubation of colonic mucosa from rats treated with arachidonic acid and stimulated with A23187 showed an increase of the cyclooxygenase product 12-hydroxy-heptadecatrienoic acid (HHT) and the 12-1ipoxygenase product (12-HETE) and a decrease in the formation of 6-keto-prostaglandin F1α(6kPGF1α) in comparison with normal rat mucosa. Malotilate, ZY16268 and ZY16369 all resulted in a decrease in HHT, leukotriene B4 (LTB4)-like compounds and 12-hydroxyeicosaenoic acid (12-HETE) production. None of the tested compounds significantly reduced the colonic damage by acetic acid although the formation of 12-HETE was proportional to the histologically obtained inflammation score. There were marked differences in eicosanoid formation patterns between rat and human mucosa, both normal and inflamed. In view of the hyperacute nature of the mucosal damage and the marked differences in eicosanoid production, acetic acid induced colitis in rats is probably not a suitable model of ulcerative colitis in humans.